The Roman Silversmith Lorenzo de Caporali and His Work in the Cathedral of Seville (BSAA arte, 2023)
This article reveals the authorship of the silver altar frontal of the chapel of Nuestra Señora de la Antigua in the cathedral of Seville. Specifically, thanks to a correct reading of its punches, we know that it was executed by the Roman silversmith Lorenzo de Caporali before September 1761, when canon Martín Alberto de Carvajal donated it to this Marian chapel. In addition, we analyse the style of the piece and argue the connection between its patron and Rome thanks to the new documents we have found in different archives.
Keywords: silverwork; Rome; 18th century; Lorenzo de Caporali; Seville Cathedral